1982
DOI: 10.3323/jcorr1974.31.11_714
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Resistance of Metallic Materials in High Temperature Gases Composed of Iodine, Hydrogen Iodide and Water (Environment of the 3rd and 4th Stage Reactions)

Abstract: In order to select candidate materials for the equipment of the 3rd and 4th reaction of Mg-I thermochemical hydrogen production cycle, screening test of metallic materials was conducted. The corrosive constituents concerned in the 3rd reaction are hydrogen iodide, iodine, and water, and in the 4th reaction, hydrogen iodide, iodine, water, and hydrogen. Therefore, for the 1st screening test, the testing environment was made up of hydrogen iodide, iodine, and water under the condition of linearly increasing temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bunsen reaction (1) produces sulfuric acid (H 2 SO 4 ) and hydrogen iodide (HI) from iodine (I 2 ), sulfur dioxide gas (SO 2 ) and raw material of water (H 2 O). H 2 SO 4 is decomposed into SO 2 , H 2 O, and product oxygen (O 2 ) by the reaction (2). Also, HI is decomposed into I 2 and product hydrogen (H 2 ) by the reaction (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunsen reaction (1) produces sulfuric acid (H 2 SO 4 ) and hydrogen iodide (HI) from iodine (I 2 ), sulfur dioxide gas (SO 2 ) and raw material of water (H 2 O). H 2 SO 4 is decomposed into SO 2 , H 2 O, and product oxygen (O 2 ) by the reaction (2). Also, HI is decomposed into I 2 and product hydrogen (H 2 ) by the reaction (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the HI decomposition reaction (3) environment, structural materials are attacked by gaseous halogen compounds such as HI and I 2 around 500°C. Candidate structural materials were e screened by corrosion resistant tests [2]- [6] in the HI decomposition reaction (3) environment. The studies found that ceramic materials such as alumina, mullite, SiC etc.…”
Section: Introductionmentioning
confidence: 99%